Outcomes of Extra Corporeal Shock Wave Lithotripsy in Renal and Ureteral Calculi - Joshi, HN; Karmacharya, Rm; Shrestha, R; Shrestha, B; De Jong, IJ; Shrestha, RKM (Kathmandu University Medical Journal, 2015)
Background Since the introduction in early 1980s, Extracorporeal Shockwave Lithotripsy (ESWL) became the accepted first line treatment modality for renal and upper ureteric stones. It is simple, safe and effective noninvasive procedure which can be performed without anaesthesia in outpatient basis. The objective of this study was to determine the efficacy of ESWL to achieve complete stone clearance in the patients with different sizes of renal and upper ureteric stones.Objective The aim of this study was to assess the outcome, efficacy and complications of ESWL in the treatment for renal and ureteric stones in terms of the site and the size of the stone in the patients presented at Dhulikhel Hospital Kathmandu University Hospital.Method In this prospective study a total of 430 (214 renal and 216 ureteric) cases of urinary stone disease in 257 male and 173 female patients treated by ESWL at Dhulikhel Hospital, Kathmandu University Teaching Hospital during time period of May 2010 to June 2012 were included. Data of patients with renal and ureteric stones were evaluated for stone site, size, and number of sessions. Data were analyzed using spss 13.0.Result Out of 430 cases, the overall stone free rate in after 1st session was 341 (79.3%) at one month and in three months follow up (3 sessions) it was increased up to 414 (96.3%). In 16 (3.7%) patients treatment was failed. Average size of the stone was 12.24 (SD± 3.65) mm.Stone free rate was 154 (72%) in the case of renal and 187 (86.6%) in the case of ureteric stones in first session. In three months follow up (three sessions) it was 204 (95.4%) and 210 (97.2%) respectively for renal and ureteric stones. In relation to size the stone free rate in 15mm was 97%, 97% and 90%.Conclusion ESWL is the first line preferred choice for renal and upper ureteric stones which provides the maximum stone free rate in the case of stone size smaller than 1.5cm.Kathmandu University Medical Journal Vol.12(1) 2014: 51-54